Item Response Theory: Psychometric Properties of Career Maturity Instruments for College Students - Arina Husna Zaini; Muchammad Ainur Rofiqi (International Conference on Psychology and Education (ICPE), 2024)
Career maturity plays an important role in an individual's efforts to achieve a career in the future, especially for students who are about to enter the workforce. However, the facts show that colleges are struggling to assist students in supporting their career maturity due to the lack of instruments to measure career maturity that possess good psychometric properties, especially for students. Thus, this research aims to investigate the psychometric properties of the career maturity instrument derived from the modification of an existing career maturity instrument. This research employs quantitative exploratory research, where to achieve the research objectives, the researcher utilizes Item Response Theory (TRB). The sample in this study consists of final-year students, with a total of 357 respondents. Data collection was carried out using a modified career maturity instrument, consisting of 24 items that have been proven to be valid in content and reliable. The research results indicate that the career maturity instrument is valid in terms of construct, where the EFA analysis results show two factors, but only one factor is dominant. From the reliability test, the career maturity instrument has a reliability index of 0.7, which falls into the high category. The difficulty level of the career maturity instrument is generally considered good. From the perspective of individual capabilities, the career maturity instrument in this study can provide optimal information when used to measure students with below-average abilities.